Development and operational verification of a lower limb rehabilitation device for preventing sarcopenia - Yusuke IMANISHI; Nobutaka TSUJIUCHI; Akihito ITO; Tomoya MUKAI (Mechanical Engineering Journal)
In recent years, there is a gap in the life expectancies between the average and the healthy populations of the aging society of Japan. One factor that influences the decline in healthy life expectancy is muscle weakness due to sarcopenia. Its symptoms tend to be accelerated when patients are forced to remain bedridden during treatment for various illnesses or injuries. Therefore, better prevention methods must be developed for sarcopenia that can be used during bed rest. This study establishes a new prevention method for sarcopenia by focusing on the soleus and gastrocnemius muscles. We developed a rehabilitation device that adjusts the ankle joint angle to a specified slant in a specified time while measuring the load on the foot. Our rehabilitation device was developed based on an orthosis to which we attached a mechanism that adjusts the ankle joint. By promoting dorsiflexion by tensing a belt fixed at two points on both the toe and knee sides, a prototype was fabricated using a servo motor as a power source. We created a control system through which the device adjusts the ankle joint angle to a target angle within a target operation time and experimentally verified the device operation with five subjects. Our prototype was able to dorsiflex and plantarflex at specified angles. Most significantly, except for a few results, both the dorsiflexion and plantar-flexion movements were completed approximately 10% more quickly than the target operation time. If we can integrate a training program that accounts for differences in muscle fibers into the device and demonstrate its effectiveness, we believe that it will contribute to the enrichment of rehabilitation methods for preventing sarcopenia in bedridden patients.